If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -93 = -2(8 + -7n) + -7 -93 = (8 * -2 + -7n * -2) + -7 -93 = (-16 + 14n) + -7 Reorder the terms: -93 = -16 + -7 + 14n Combine like terms: -16 + -7 = -23 -93 = -23 + 14n Solving -93 = -23 + 14n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-14n' to each side of the equation. -93 + -14n = -23 + 14n + -14n Combine like terms: 14n + -14n = 0 -93 + -14n = -23 + 0 -93 + -14n = -23 Add '93' to each side of the equation. -93 + 93 + -14n = -23 + 93 Combine like terms: -93 + 93 = 0 0 + -14n = -23 + 93 -14n = -23 + 93 Combine like terms: -23 + 93 = 70 -14n = 70 Divide each side by '-14'. n = -5 Simplifying n = -5
| -7=-.5 | | 67+t= | | 5x^2-15x-216=0 | | 4m+14=-3m+49 | | X-10+7x=10 | | 26-5n=2-2n | | 13-r=9 | | 0.125(x)=150 | | 4n-8n+4n= | | 4f^2+4f-48=0 | | Y+6=2(x-5) | | 2a=12.4 | | x^2-14x=-5 | | m-3+5=-2 | | x(22)+12=56 | | Y=-3(x-5) | | 8(7n-5)+4(1-3n)=-80 | | 4s^2+16s=148 | | x=3ln((y^2)-24) | | 7a^2=42+7a | | 2y=14x-10 | | 5x-13=4-5x | | p=-0.5x^2+36x-91 | | 5x-15=4-8x | | 8y-12=2y+6 | | 17x+50+5x=-1+x | | 5x-15=4-6x | | u^2-17u-43=0 | | 5x-15=4-4x | | 9+2x-1=4x-4 | | 12x+6y+7z=-35 | | 16(3.2-x)=4x+15 |